1
$\begingroup$

Below is a problem from the book Differential Equations written by K.A. Stroud and Dexter Booth. It can be found on page 65 of the book. My answer matches the book's answer but I am not sure I did it correctly, especially the last part.
Thanks,
Bob

Problem:
Obtain the general solution of the equation $$ \frac{d^2y}{dt^2} + 4\frac{dy}{dt} + 5y = 6 \sin t$$ and determine the amplitude and frequency of the steady-state function.
Answer:
Our approach is to find $y_c$ which is the complimentary solution and then find $y_p$ which is the particular solution. Then our solution will be $y = y_c + y_p$. We have the following characteristic equation: $$ m^2 + 4m - 5 = 0 $$ We then solve it by applying the quadratic formula. \begin{align*} m &= \frac{-4 \pm \sqrt{16-4(1)(5)}}{2(1)} = \frac{-4 \pm \sqrt{16-20}}{2} \\ m &= \frac{-4 \pm \sqrt{-4}}{2} \\ m &= -2 \pm i \\ y_c &= e^{-2t}(C_1 \cos t + C_2 \sin t) \\ \end{align*} \begin{align*} y_p &= A \sin t + B \cos t \\ y'_p &= A \cos t - B \sin t \\ y''_p &= -A \sin t - B \cos t \\ \end{align*} \begin{align*} -A \sin t - B \cos t + 4( A \cos t - B \sin t ) + 5( A \sin t + B \cos t ) &= 6 \sin t \\ -A \sin t - B \cos t + 4A \cos t - 4B \sin t + 5A \sin t + 5B \cos t &= 6 \sin t \\ 4A \sin t - B \cos t + 4A \cos t - 4B \sin t + 5B \cos t &= 6 \sin t \\ \end{align*} Now we solve for $A$ and $B$. \begin{align*} 4A - 4B &= 6 \\ -B + 4A + 5B &= 0 \\ 4A + 4B &= 0 \\ A &= -B \\ 4(-B) - 4B &= B \\ -8B &= 6 \\ B &= -\frac{3}{4} \\ A &= \frac{3}{4} \\ y_c &= \frac{3}{4} \sin t - \frac{3}{4} \cos t \\ \end{align*} Hence the solution we seek is: $$ y = e^{-2t}(C_1 \cos x + C_2 \sin x) + \frac{3}{4} \sin t - \frac{3}{4} \cos t $$ Now the problem asks for the amplitude of the steady-state function. Observe that: $$ \lim_{t \rightarrow \infty} y = \frac{3}{4} \sin t - \frac{3}{4} \cos t$$ Let $y_1 = \frac{3}{4} \sin t - \frac{3}{4} \cos t$. To find the amplitude, I want to find the minimum and maximum of $y_1$. \begin{align*} y'_1 &= \frac{3}{4} \cos t + \frac{3}{4} \sin t = 0 \\ \cos t + \sin t &= 0 \\ \cos t + \sqrt{ 1 - \cos^2{t} } &= 0 \\ \cos t &= - \sqrt{ 1 - \cos^2 t } \\ \cos ^2 t &= 1 - \cos^2 t \\ 2 \cos^2 t &= 1 \\ \cos t &= \pm \frac{ \sqrt{2} } {2} \\ % t &= \pm \frac{\pi}{4} \\ % y_1( \frac{\pi}{4} ) &= \frac{3}{4} \sin{ \frac{\pi}{4} } - \frac{3}{4} \cos { \frac{\pi}{4} } \\ % y_1( \frac{\pi}{4} ) &= \frac{3 \sqrt{2}}{4(2)} - \frac{3 \sqrt{2} }{4(2)} \\ % y_1( -\frac{\pi}{4} ) &= \frac{3}{4} \sin{ fixme } - \frac{3}{4} \cos { fixme } \\ \end{align*} Now we need to consider the following four values for $t$ to find the maximum and minimum of $y$: $$ \frac{\pi}{4} \, , \, \frac{3\pi}{4} \, , \, \frac{5\pi}{4} \, , \, -\frac{\pi}{4} $$ \begin{align*} y_1 \left( \frac{\pi}{4} \right) &= \frac{3}{4} \sin{ \frac{\pi}{4} } - \frac{3}{4} \cos { \frac{\pi}{4} } \\ y_1 \left( \frac{\pi}{4} \right) &= \frac{3 \sqrt{2}}{4(2)} - \frac{3 \sqrt{2} }{4(2)} = 0 \\ % y_1 \left( \frac{3\pi}{4} \right) &= \frac{3}{4} \sin{ \frac{3\pi}{4} } - \frac{3}{4} \cos { \frac{3\pi}{4} } \\ y_1 \left( \frac{3\pi}{4} \right) &= \frac{3 \sqrt{2}}{4(2)} - \frac{-3 \sqrt{2} }{4(2)} \\ y_1 \left( \frac{3\pi}{4} \right) &= \frac{3 \sqrt{2}}{4(2)} + \frac{3 \sqrt{2} }{4(2)} = \frac{3\sqrt{2}}{4 } \\ % y_1 \left( \frac{5\pi}{4} \right) &= \frac{3}{4} \sin{ \frac{5\pi}{4} } - \frac{3}{4} \cos { \frac{5\pi}{4} } \\ y_1 \left( \frac{5\pi}{4} \right) &= -\frac{3 \sqrt{2}}{4(2)} - \frac{-3 \sqrt{2} }{4(2)} \\ y_1 \left( \frac{5\pi}{4} \right) &= 0 \\ % y_1 \left( -\frac{\pi}{4} \right) &= \frac{3}{4} \sin{ -\frac{\pi}{4} } - \frac{3}{4} \cos { -\frac{\pi}{4} } \\ y_1 \left( -\frac{\pi}{4} \right) &= \frac{-3 \sqrt{2}}{4(2)} - \frac{3 \sqrt{2} }{4(2)} \\ y_1 \left( -\frac{\pi}{4} \right) &= -\frac{3\sqrt{2}}{4 } \\ \end{align*} Hence, we have a minimum at $t = -\frac{\pi}{4}$ and a maximum at $t = \frac{3\pi}{4}$. The amplitude is one half of the difference of the function at its maximum and the value of the function at its minimum. In this case the amplitude is: $$ \frac{ 3\sqrt{2} }{4} $$

Now we need to find the frequency of the function $y_1$. The period of both $\sin$ and $\cos$ is both $ 2\pi $. Our function is the difference of two functions with a period of $ 2 \pi $. Therefore the period of $y_1$ is $$ \frac{1}{2 \pi}$$

$\endgroup$
  • 1
    $\begingroup$ I think most of what you have looks correct. I would look at how to calculate the period. $1/2\pi$ doesn't sound right to me. One easy way to check yourself is to plot your function to see what the period is. It should be $2\pi$. $\endgroup$ – D.B. Jan 13 at 23:18
  • $\begingroup$ @D.B. When I wrote period, I meant frequency. Does a frequency of $\frac{1}{2 \pi}$ seem right to you? $\endgroup$ – Bob Jan 13 at 23:57
  • 1
    $\begingroup$ Indeed. Once complete cycle for every $2\pi$ units. $\endgroup$ – D.B. Jan 13 at 23:58
1
$\begingroup$

You're overthinking it

$$ y_\infty (t) = \frac34 (\sin t - \cos t) = \frac{3}{2\sqrt{2}}\left(\frac{1}{\sqrt 2}\sin t - \frac{1}{\sqrt 2}\cos t \right) = \frac{3}{2\sqrt 2}\sin\left(t - \frac{\pi}{4} \right) $$

So the amplitude of the steady-state is $\frac{3}{2\sqrt 2}$. In general, you may use

$$ A\sin t + B\cos t = \sqrt{A^2+B^2}\left(\cos\phi\sin t +\sin\phi\cos t\right) = \sqrt{A^2+B^2}\sin\left(t + \phi\right) $$

where $\cos\phi = \frac{A}{\sqrt{A^2+B^2}}$ and $\sin \phi = \frac{B}{\sqrt{A^2+B^2}}$

The amplitude/frequency is straightforward.

$\endgroup$
  • 1
    $\begingroup$ Yes. I'm agree with this too.... $\endgroup$ – Mostafa Ayaz Jan 14 at 9:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.